Assessing the Implemention Success of Official Travel Management System at Directorat General of Budget, Ministry of Finance, Republic of Indonesia - Azizah Zulfika; Christina Dwi Astuti (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2025)
An effective information system is essential for promoting public service delivery and bureaucratic efficiency. In particular, a strong information system can improve the quality of budget execution in the context of official travel procedures. Using the Information Systems Success Model put forward by DeLone and McLean (2003), this study aims to evaluate the efficacy of the Directorate General of Budget's official travel management system installation. This model states that a number of causally related dimensions, including system quality, information quality, service quality, user satisfaction, and net benefits, can be used to gauge an information system's success. The primary variables in this study are these five dimensions. The Directorate General of Budget has been using the official travel management system since April 2024, but no thorough quantitative study using this model has been conducted as of yet. This study also examines whether user satisfaction mediates system quality, information quality and service quality with regard to net benefits. Data were collected by online survey with Google Forms among 110 staffs who had previously used the system in Directorate General of Budget. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed to analyze the data and SmartPLS software was used for investigations. Results suggest that if the technical capability of the system is enhanced to satisfy users’ requirements, then users would be more satisfied and increase overall system performance